Effect of Mirror Therapy on Phantom Pain Levels in Post Amputation Patient: a Literature Review - Jon Hafan Sutawardana; Siswoyo Siswoyo; Wantiyah Wantiyah; Fahruddin Kurdi; Murtaqib Murtaqib; Dwi Ayu Sari; Ana Nistiandani (NurseLine Journal, 2022)
Background: Phantom pain after amputation is ordinary. Phantom pain is challenging to treat, so it will last a long time which will cause depression and anxiety and reduce the quality of life. There are various treatment options: pharmacological (antidepressants, anesthetics) and non-pharmacological (acupuncture, hypnosis). However, there is still no proven effective therapy, so it is necessary to try a non-pharmacological therapy that is safe, cheap, and easy, namely mirror therapy. Purpose: This study aims to determine how the effect of mirror therapy on the phantom pain of post-amputation patients. Methods: Narrative literature review of a publication registered 2017-2021 on Pubmed, ProQuest, EBSCO, and Google Scholar. Search articles using the keywords" amputation," and " phantom pain," and "mirror therapy." This study uses inclusion criteria consisting of patients who experience phantom pain, research in the form of mirror therapy intervention, there is comparison, the study design uses a randomized controlled trial and case report, with results explaining the effect of mirror therapy in Indonesian or English, and indexed by SINTA or SCIMAGO. Results: 8 articles were included in the inclusion criteria. The majority of articles had a randomized controlled trial design of 7 articles and a case report of 1 article. Four articles discuss mirror therapy, and the other four articles discuss mirror therapy with other therapies. Respondents have an age range of 15-82 years, and most are male. Conclusion: Mirror therapy is recommended to be carried out routinely and according to procedures for post-amputation patients. It has been proven to reduce pain scales in patients before and after the intervention. Nurses can use mirror therapy in the client care process during the post-amputation rehabilitation process.